O Processo Reflexivo-Colaborativo na Formação Inicial de Professores de Português Língua Estrangeira - Anelise Fonseca Dutra (2010)
This study aims at researching the pre-service teacher education of Portuguese as a foreign language. It is based on reflexive practice, collaborative work and critical reflection. The objective of working with pre-service teachers was the possibility of offering a course that joins theory and practice from the very beginning. The methodology used in this ethnographic research involved shooting of classes, collaborative sections, use of diaries and semi-structured interviews with four pre-service teachers from the Centro de Extensão at Faculdade de Letras, UFMG. Data was collected during a period of a year, divided into two Modules. In the first module the teachers worked in pairs, each of which took over a group. The teachers worked collaboratively in the preparation, application and discussion of each class. In the second module, the teachers worked individually in their classes, but with a weekly collaboration of the other teacher during the collaborative sections. The researcher was present, as the supervisor of the training course, in the shooting of the lessons and in the collaborative sections. The results of the research show that a pre-service training course for teachers of Portuguese as a foreign language involving a reflexive-collaborative process may cause changes in the beliefs and in the pedagogical practices of the teachers. Furthermore, this reflexive-collaborative work helps the teacher in the development of a critical view of himself as a Brazilian teacher and of the foreign student. The results of this research offer theoretical grounds that may help in the creation of a model of professional development for the teacher of Portuguese as a foreign language.